New approaches to changing the sorption properties of loess rocks - Mavlyanov G.N.; Mavlyanov P.N. (The Bioscan, 2024)
The purpose of the study: to study the change in the absorption capacity and sorption properties of loess rocks when introducing an organomineral complex Object and methods of the study.The irrigated areas of the Verkhnechirchik district of the Tashkent region were chosen as the object of the study. A series of field works were carried out, during which the composition of the soil, the dose of the organomineral complex and nitrogen fertilizer were changed. Results of the study. The results of lysimetric studies showed that the introduction of OMC on the background of N200P140K100 has a significant effect on the transformation of nitrogen compounds in the soil. When introduced at rates of 10 and 15 t / ha, the content of ammonia nitrogen in the soil significantly increases compared to the control at all times of determination. Thus, in the arable layer of the variants with the introduction of the organomineral complex (OMC) at rates of 10 and 15 t/ha, the content of ammonia nitrogen in the 3rd quarter of 2021 was, respectively, 15.8 and 20.1 mg, in the 4th quarter 11.7 and 13.4 mg, in the 1st quarter of 2016 10.4 and 12.2 mgagainst 6.4-7.2 mgin the control. Conclusions: Thus, the introduction of OMC helps to reduce the formation of nitrites and nitrates in the aeration zone, which serves to prevent their leaching into groundwater and underground water. The use of OMC is an effective mechanism for eliminating excess nitrate concentrations in the aeration zone and accumulating nitrogen in ammonium and organic form.